Speed of radio wave propagation in dry and wet snow - V. M. Kotlyakov; Yu. Ya. Macheret; A. V. Sosnovsky; A. F. Glazovsky (Лëд и снег, 2017)
In recent years, ground-penetrating radars are widely used for measuring thickness and liquid water content in snow cover on land and glaciers. The measurement accuracy depends on radio wave velocity (RWV) adopted for calculations. The RWV depends mainly on density, water content and structure of the snow cover and ice layers in it. The density and wetness of snow, and its structure can be estimated from data on RWV, using the available experimental and theoretical relations. Satisfactory results can be obtained using the Looyenga’s (1965) equations to estimate the density and wetness of snow cover, and equations of van Beek’s (1967) showing the distinction between RWV speeds velocities in snow cover and ice layers with different prevailing orientation and sizes of air or water inclusions.RWV in dry snow with density 300 kg/m3 may vary by 32 m/µs, depending on whether the vertical or horizontal orientation of the air inclusions prevails therein. In ice with density 700 kg/m3 effect of air inclusions orientation on differences in RWV is reduced to 5 m/µs. If the inclusions are not filled with air but with water, the difference in RWV in snow is 21 m/µs, and in ice is 24 m/µs. The RWV is affected not only by orientation of the inclusions, but their elongation. Twofold elongation of ellipsoidal air and water inclusions increases the difference in RWV in snow (with a density 300 kg/m3 ) to 23 m/µs and 22 m/µs.These estimates show a noticeable influence of snow structure on RWV in snow cover. The reliability of the above RWV estimates depends significantly on a thermal state of the snow cover, and decreases during snowmelt and increases in the cold period. It strongly depends on accuracy of measurements of the RWV in snow cover and its separate layers. With sufficiently high accuracy of the measurements this makes possible to detect and identify loose layers of deep hoar and compact layers of infiltration and superimposed ice, which is important for studying the liquid water storage of snow cover and a glacier mass balance. Therefore, considerable attention should be given to accuracy of the RWV measurements in dry and wet snow cover and its individual layers. With sufficiently high accuracy of measurements of the RWV, this should allow revealing such layers and estimating their thickness and average density.